Teacher Independence Program In Improving Community Trust - Muslimin Muslimin; Syafik Ubaidila (eL Bidayah: Journal of Islamic Elementary Education, 2020)
This type of research is descriptive qualitative. According to Kirt and Miller in his book Lexy J. Moleong, "Qualitative research is that researchers have studied the phenomena studied by natural settings. Therefore, the data raised in the form of description with words, both oral and written language. While the data collection method uses observation, interviews / interviews and documentation. Then analyzed using descriptive / data exposure. From the results of data exposure, research findings and discussion can be seen that: {1} the increase in teacher independence in MI Al Munir Gadungan Village is seen in several activities, namely [a] through preparation of learning by preparing RPP in accordance with applicable SK and KD, [b] increase teacher creativity in developing learning strategies. [c] teacher creativity in choosing and using learning methods ,. [d] The creativity of the teacher in selecting and using learning media is very important to do, [e] the creativity of the teacher in class management. Classroom management with preventive and curative techniques, [f] teacher creativity in assessment; and [g] teacher creativity in improvement and enrichment programs. {2} The factors that support and hinder the teacher's personality improvement program. [Jenis penelitian ini adalah kualitatif diskriptif. Menurut Kirt dan Miller dalam bukunya Lexy J. Moleong, “penelitian kualitiatif adalah udaha peneliti mendalami fenomena yang diteliti dengan seting natural. Karena itu, data yang dimunculkan berupa diskripsi dengan kata, bahasa baik lisan maupun tulisan. Sedangkan metode pengumpulan data menggunakan observasi, wawancara/ interview dan dokumentasi. Kemudian dianalisis menggunakan deskriptif / paparan data. Dari hasil paparan data, temuan penelitian dan pembahasan dapat diketahui bahwa: {1} peningkatan kemandirian guru di MI Al Munir Desa Gadungan terlihat dalam beberapa kegaitan yaitu [a] melalui persiapan permbelajaran dengan penyusunan RPP sesuai dengan SK dan KD yang berlaku, [b] meningkatkan kreativitas guru dalam mengembangkan strategi pembelajaran. [c] kreativitas guru dalam memilih dan menggunakan metode pembelajaran,. [d] Kreativitas guru dalam memilih dan menggunakan media pembelajaran sangat penting untuk dilakukan, [e] kreativitas guru dalam pengelolaan kelas. Pengelolaan kelas dengan teknik preventif dan kuratif, [f] kreativitas guru dalam penilaian; dan [g] kreatifitas guru dalam program perbaikan dan pengayaan. {2} Faktor yang mendukung dan menghambat program peningkatan kepribadian guru]